Boston Coliseum, Copley Square, ca. 1869 - Unknown (Tufts Archival Research Center, 2005)
Elevated view of the Boston Coliseum, built to hold the National Peace Jubilee in 1869. The building is located to the southeast of Copley Square at Dartmouth and Boylston Streets. The facade of the coliseum faces north-northwest towards Boylston Street. Debris and construction equipment cover the ground surrounding the coliseum. Designed by William Gibbons Preston; coliseum constructed for the International Peace Jubilee, June 17, 1872 - July 4, 1872; building measurements: Length - 550 feet, Width - 350 feet, Seating capacity - 50,000, Area of building - 4 1/2 acres 2 1/8 x 3 1/2, 2 15/16 x 4 1/8 overall Cartes-de-visite